Juglone induces apoptosis and autophagy via modulation of mitogen-activated protein kinase pathways in human hepatocellular carcinoma cells. (June 2018) - Wang, Peng; Gao, Chang; Wang, Wei; Yao, Li-Ping; Zhang, Jing; Zhang, Sun-Dong; Li, Ji; Fang, Shao-Hong; Fu, Yu-Jie
Abstract: Juglone (JG), a naturally-occurring naphthoquinone of Manchurian walnut ( Juglans mandshurica ) was shown to inhibit proliferation in various tumor types. However, the molecular mechanisms of JG on the induction of apoptosis and autophagy in HepG2 cells have not been examined. Herein, we investigated that JG could inhibit cell proliferation by induction of G2/M phase arrest. Also, occurrence of apoptosis was closely related with loss of mitochondrial membrane potential, the changes of apoptosis-related proteins after treatment with JG. In addition, we found that JG caused autophagy, as evidenced by increased expressions of LC3-II and Beclin-1. Interestingly, inhibition of JG-induced autophagy by 3-methyladenine (3-MA) and wortmannin (WT) significantly decreased apoptosis, whereas the apoptosis inhibitor z-VAD-fmk slightly enhanced autophagy. Furthermore, the induction of autophagy and apoptosis was associated with activation of MAPK family members (p38 and JNK) and production of reactive oxygen species (ROS). Both JNK inhibitor (SP600125) and ROS scavenger (N-acetylcysteine, NAC) could attenuate JG-induced autophagy and apoptosis. However, the p38-specific inhibitor SB203580 enhanced autophagic and apoptotic death. Moreover, the ROS scavenger NAC prevented phosphorylation of both p38 and JNK. Collectively, our data revealed that JG induced G2/M phase arrest, apoptosis, and autophagy through the ROS-dependent signaling pathway. Graphical abstract: Highlights: JG-induced ROS production caused oxidative damage to mitochondria and DNA. JG kills HepG2 cells through the induction of apoptosis. JG triggers autophagy, which contributes to JG-induced cell death. The autophagic cell death was dependent on ROS generation and the activation of p38 MAPK and JNK pathways. JG is a potential therapeutic agent for the treatment of HCC.